# Page:A Treatise on Electricity and Magnetism - Volume 1.djvu/203

different ways, and if we do so to all the terms, we shall obtain the whole permutations of $i$ symbols, the number of which is $|\underline{i}$. Let the sum of all terms of this kind be written in the abbreviated form

$\sum\left(\lambda^{i-2s}\mu^{s}\right).$

If we wish to express that a particular symbol $j$ occurs among the $\lambda$’s only, or among the $\mu$’s only, we write it as a suffix to the $\lambda$ or the $\mu$. Thus the equation

 $\sum\left(\lambda^{i-2s}\mu^{s}\right)=\sum\left(\lambda_{j}^{i-2s}\mu^{s}\right)+\sum\left(\lambda^{i-2s}\mu_{j}^{s}\right)$ (16)

expresses that the whole system of terms may be divided into two portions, in one of which the symbol $j$ occurs among the direction-cosines of the radius vector, and in the other among the cosines of the angles between the axes.

Let us now assume that up to a certain value of $i$

 $\begin{array}{ll} Y_{i}=A_{i.0}\sum\left(\lambda^{i}\right) & +A_{i.1}\sum\left(\lambda^{i-2}\mu^{1}\right)+\mathrm{etc}.\\ \\ & +A_{i.s}\sum\left(\lambda^{i-2s}\mu^{s}\right)+\mathrm{etc}.\end{array}$ (17)

This is evidently true when $i=1$ and when $i=2$. We shall shew that if it is true for $i$ it is true for $i+1$. We may write the series

 $Y_{i}=S\left\{ A_{i.s}\sum\left(\lambda^{i-2s}\mu^{s}\right)\right\} ,$ (18)

where $S$ indicates a summation in which all values of $s$ not greater than $\tfrac{1}{2}i$ are to be taken.

Multiplying by $|\underline{i}\ r^{-(i+1)}$, and remembering that $p_{i}=r\lambda_{i}$, we obtain by (14), for the value of the solid harmonic of negative degree, and moment unity,

 $V_{i}=|\underline{i}\ S\left\{ A_{i.s}r^{2s-2i-1}\sum\left(p^{i-2s}\mu^{s}\right)\right\}$ (19)

Differentiating $V_i$ with respect to a new axis whose symbol is $j$, we should obtain $V_{i+1}$ with its sign reversed,

 $-V_{i+1}=|\underline{i}\ S\left\{ A_{i,s}(2s-2i-1)r^{2s-2i-3}\sum\left(p_{j}^{i-2s+1}\mu^{s}\right)+A_{i,s}r^{2s-2i-1}\sum\left(p^{i-2s-1}\mu_{j}^{s+1}\right)\right\} .$

If we wish to obtain the terms containing $s$ cosines with double suffixes we must diminish $s$ by unity in the second term, and we find

 $-V_{i+1}=|\underline{i}\ S\left\{ r^{2s-2i-3}\left[A_{i,s}(2s-2i-1)\sum\left(p_{j}^{i-2s+1}\mu^{s}\right)+A_{i,s-1}\sum\left(p^{i-2s+1}\mu_{j}^{s}\right)\right]\right\} .$ (21)

If we now make

 $A_{i,s}(2s-2i-1)=A_{i,s-1}=-(i+1)A_{i+1.s}$ (22)

then

 $V_{i+1}=|\underline{i+1}S\left\{ A_{i+1.s}r^{2s-2(i+1)-1}\sum\left(p^{i+1-2s}\mu^{s}\right)\right\} ,$ (23)

and this value of $V_{i+1}$ is the same as that obtained by changing $i$